2017
DOI: 10.1016/j.dld.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

HCV clearance after direct-acting antivirals in patients with cirrhosis by stages of liver impairment: The ITAL-C network study

Abstract: Our findings support the use of DAAs in patients with advanced cirrhosis (stages 3-5) who are at greatest risk and have the most to gain from therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
(35 reference statements)
3
27
0
Order By: Relevance
“…Information on treatment outcome was available for 228 of the 240 Child C patients evaluated in the 10 trials. The SVR12 rates described in the individual studies are shown in Figure : the rates varied from low values of 50.0% and 56.3% reported in two studies to high values of 94.4% and 96.0% found in two other reports . Overall, the weighted mean SVR12 rate was 74.9% (95% CI: 65.6–82.4%) using a random effects model.…”
Section: Resultsmentioning
confidence: 93%
“…Information on treatment outcome was available for 228 of the 240 Child C patients evaluated in the 10 trials. The SVR12 rates described in the individual studies are shown in Figure : the rates varied from low values of 50.0% and 56.3% reported in two studies to high values of 94.4% and 96.0% found in two other reports . Overall, the weighted mean SVR12 rate was 74.9% (95% CI: 65.6–82.4%) using a random effects model.…”
Section: Resultsmentioning
confidence: 93%
“…Diagnosis of advanced liver fibrosis was based on liver transient elastography and histological evaluation, when available, as previously described . Briefly, advanced fibrosis (F3) was indicated by liver stiffness measurement ranging from 10 to 14 kPa and platelets >100 000/µL, in the absence of hepatic decompensation and ultrasound signs of portal hypertension while patients were considered to have cirrhosis when transient elastography values were >14.0 kPa and platelet counts ≤140 000/μL as well as when transient elastography values were 10‐14 kPa and platelet counts ≤100 000/μL.…”
Section: Methodsmentioning
confidence: 99%
“…Our prospective observational study, deriving from a larger study performed by a consortium of several community and academic Italian medical centres examining the impact of DAA treatment in HCV‐infected patients, focused on the clinical implications of SOF/LED treatment duration. The collection of data on consecutive HCV genotype 1b‐infected patients with cirrhosis started in June 2015, when second‐generation SOF/LED combination therapy received regulatory approval in Italy from the Agenzia Italiana del Farmaco (AIFA), and ended in August 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Our prospective observational study, deriving from a larger study performed by a consortium of several community and academic Italian medical centres examining the impact of DAA treatment in HCVinfected patients, 18 baseline characteristics of patients treated for 12 weeks were significantly different from those treated for 24 weeks as regards their younger age (P = .002), prevalence of Child-Pugh class A (P = .002), lower MELD scores (P = .001) and smaller number of nonresponders (P = .04). The shorter treatment was significantly associated with a lower SVR12 in univariate and multivariate analyses (P = .007 and P = .008, respectively).…”
Section: Methodsmentioning
confidence: 99%